PENGELOLAAN SUMBERDAYA AIR DI KABUPATEN LOMBOK BARAT: SEBUAH POTRET IMPLEMENTASI KEBIJAKAN EKONOMI HIJAU - Sudiyono, Sudiyono (P2KK LIPI, 2012)
This article discusses water scarcity that occured in West Nusa Tenggara Province, particularly in West Lombok District. The main cause of this nature calamity was the forest destruction at the upstream area. To overcome this problem, the West Lombok District Government have issued water resource management policy, popularly known as “Green Economy Policy”. According to the UNEP, the concept of green economy is one effort to improve human well-being and social equity, while at the same time may significantly reduce environmental risks and ecological scarcities. In other words, green economy is the new paradigm of nature resource management, which shifts this sectoral approach to integrated management. Implementation of this programs are as follows; reforestation at the water catchment area, planting of mangrove trees, village self-help energy program (program desa mandiri energi), thousand blue programs (program seribu biru), and environment public services program. How this program is carried out by the West Lombok District Government? This article aims to answer the question. Keywords: water scarcity, water resource management, green economy.